Identification of threats to the financial security of banks - Lelyuk, Natalia; Rodchenko, Svitlana (Technology audit and production reserves, 2018)
The object of research is the internal and external threats to the financial security of Ukrainian banks. One of the biggest problems of banking institutions is the presence of threats and their identification and ranking in order of importance, significance and impact on financial security. In the course of research, the following methods are used: abstract-logical, comparative analysis, statistical, monographic, expert assessments, graphical, tabular, dialectical. For risk analysis, a system of indicators is proposed, which are formed taking into account the methods of decomposition, analysis and synthesis. In identifying threats to field research, an analysis of the literature of specialists in the field of financial security of banks is applied. The studies are based on the following hypothesis: for commercial banks, which differ in the form of ownership, the structure of their own capital, and the group into which the bank belongs, various threats and dangers will dominate. This requires mandatory consideration when assessing the level of financial security and developing appropriate management decisions and justifying measures to improve it. The obtained result is in identification of the most significant threats to the financial security of a commercial bank from the point of view of banking practitioners. This is due to the fact that the prioritization of threats to the financial security of banks, the determination of the degree of importance and the strength of the impact will help to form the basis for the selection of early warning and countermeasures. As well as developing strategic and tactical alternatives to ensure an adequate level of financial security. The proposed classification of threats, which takes into account the assessment of the level of importance and the importance of threats by bank employees of different qualifications and management level. The proposed classification of threats is universal for all banking institutions in different regions.